Hypoglycaemic and antioxidant effects of onion, Allium cepa: dietary onion addition, antioxidant activity and hypoglycaemic effects on diabetic rats - Campos, K. E.; Diniz, Y. S.; Cataneo, A. C.; Faine, L. A.; Alves, MJQF; Novelli, ELB (Carfax Publishing, 2003)
The purpose of the present study was to discover the relative potency of onion, Allium cepa, with respect to its hypoglycaemic and hypolipidaemic effects on the diabetic situation, and the association of these effects with the potential against oxidative stress. Male Wistar rats were divided into four groups. A normal control ( group A), and a non-diabetic group ( group B) were treated daily with 1 ml A. cepa solution (0.4 g A. cepa/rat). Groups C and D were made diabetic by an intraperitoneal injection of streptozotocin (STZ) ( 60 mg/kg body weight) in citrate buffer ( pH 6.3). These animals ( groups C and D) were the STZ diabetic control and STZ diabetic rats with onion intake, respectively. Onion increased the fasting serum high-density lipoprotein levels, and demonstrated alleviation of hyperglycaemia in STZ diabetic rats. The hypoglycaemic and hypolipidaemic actions of A. cepa were associated with antioxidant activity, since onion decreased superoxide dismutase activities while no increased lipid hydroperoxide and lipoperoxide concentrations were observed in diabetic rats treated with A. cepa.